Modulation of Starch Digestibility in Breakfast Cereals Consumed by Subjects with Metabolic Risk: Impact on Markers of Oxidative Stress and Inflammation during Fasting and the Postprandial Period. Issue 12 (7th November 2017) - Lambert‐Porcheron, Stéphanie; Normand, Sylvie; Blond, Emilie; Sothier, Monique; Roth, Hubert; Meynier, Alexandra; Vinoy, Sophie; Laville, Martine; Nazare, Julie‐Anne
Abstract: Scope : Decreasing postprandial glycaemic excursions may have a beneficial effect on inflammatory and oxidative stress profiles. In this study, we investigated the impact of carbohydrate digestibility modulation per se, as a means of reducing the glycaemic response, on metabolic and inflammatory responses in subjects with metabolic risk factors. Methods and results : Twenty healthy subjects with metabolic risk consumed a cereal product either high in Slowly Digestible Starch (HSDS) or low in SDS (LSDS) at breakfast daily for 3 weeks, in a cross‐over design. Following each 3‐week session, postprandial glycaemia, insulinaemia, the lipid profile, inflammation and oxidative stress markers were assessed and compared to those induced by ingestion of a glucose solution (as a reference). The 2‐h glycaemic and insulinaemic responses were significantly lower following the HSDS breakfast compared with the LSDS breakfast or glucose. No significant differences between the products were observed in terms of the lipid profile, C‐reactive protein, IL‐6 and tumour necrosis factor alpha. We observed a slight increase in fasting lipid peroxidation markers, including an increase in plasma malondialdehyde (MDA) and a decrease in whole blood glutathione (GSH), without significant alteration of urinary F2‐isoprostanes or plasma glutathione peroxidase (GPx) activity. Conclusion : Consumption of HSDS products for 3 weeks significantly altered both postprandial glycaemia and insulinaemia, but was not sufficient to modify the inflammatory profile. Consumption of both cereal products was associated with a slightly higher fasting oxidative stress profile. Abstract : The impact of carbohydrate digestibility per se, as a mean to reduce glycaemic response, on metabolic and inflammatory responses is investigated. Twenty healthy subjects with high metabolic risk consumed a cereal product either high in slowly digestible starch (HSDS) or without SDS (LSDS) for breakfast daily for tree weeks in a cross‐over design. HSDS products' consumption significantly alters postprandial glycaemia and insulinemia, but is not sufficient to modify the inflammatory profile. Both cereal products are associated with a slight increase in fasting oxidative stress markers.